Reformulation of Some Finite Raytracing Equations Through Quadric Surfaces of Revolution - Sadiq, Ibrahim A (Al-Nahrain Journal of Science, 2012)
This work exhibits analytical reformulation of four equations of finite raytracing through quadric surfaces of revolution. This reformulation enhances comprehending the procedure of finite raytracing firmly besides it shows how to obtain these formulas. The equations reformulated in this work clarified that the corresponding ones in [1] were merely typographically incomplete equations.